Lag coefficient of bimetal thermometer of chronometric radiosonde (MAUSAM, 1954)
The value  of  lag  coefficient of  the bimetal   thermometer   used in chronometric  radiosonde of the India Meteorological Department when it is exposed at various orientations to air currents  with different speeds has been determined experimentally. The order of errors that may be expected   due to lag at different pressure levels  has also been computed.